2014
DOI: 10.1088/0004-637x/783/2/77
|View full text |Cite
|
Sign up to set email alerts
|

OBSERVATIONAL RESULTS OF A MULTI-TELESCOPE CAMPAIGN IN SEARCH OF INTERSTELLAR UREA [(NH2)2CO]

Abstract: In this paper, we present the results of an observational search for gas phase urea [(NH 2 ) 2 CO] observed towards the Sgr B2(N-LMH) region. We show data covering urea transitions from ∼100 GHz to 250 GHz from five different observational facilities: BIMA, CARMA, the NRAO 12 m telescope, the IRAM 30 m telescope, and SEST. The results show that the features ascribed to urea can be reproduced across the entire observed bandwidth and all facilities by best fit column density, temperature, and source size paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 42 publications
(48 reference statements)
0
56
0
Order By: Relevance
“…From this exhaustive study of the relative energies of the compounds that can be formed from the CH 4 N 2 O set of atoms, we found that there is no theoretical reason not to believe that the molecule observed towards the Sgr B2-LMH region during the multi-telescope campaign by Remijan et al (2014) is not urea. Following the same reasoning, thiourea is the sulphur analogue molecule to search for.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 90%
See 2 more Smart Citations
“…From this exhaustive study of the relative energies of the compounds that can be formed from the CH 4 N 2 O set of atoms, we found that there is no theoretical reason not to believe that the molecule observed towards the Sgr B2-LMH region during the multi-telescope campaign by Remijan et al (2014) is not urea. Following the same reasoning, thiourea is the sulphur analogue molecule to search for.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 90%
“…The important result that we suppose can be generalized to all environments is that the lower energy paths go through a tautomeric form of urea. At all events, the observations of urea in gas phase reported by Remijan et al (2014) are of utmost importance. In an earlier article, we suggested guidelines for "optimizing" the hunt of new species in the interstellar medium (ISM) by identifying the potentially more abundant isomers of a given chemical formula, i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The methyl-substituted analog-acetamide (CH 3 CONH 2 )-was observed toward Sgr B2(N) with fractional abundances of 2×10 −11 to 2×10 −10 (Hollis et al 2006;Halfen et al 2011); a tentative detection of urea (CO(NH 2 ) 2 ) was reported by Remijan et al (2014) toward Sgr B2(N-LMH). Also, the very first mass spectra measured on a comet (67P/Churyumov Gerasimenko) revealed four new complex organic molecules (COM)-two of them (formamide and acetamide) carrying the peptide bond (Goesmann et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…If one is interested in molecules in the interstellar medium (ISM), the list of organic and biological molecules detected is continually becoming larger. In addition to the well-known disputed case of the simplest amino acid, glycine (Kuan et al 2003;Snyder et al 2005;Cunningham et al 2007;Jones et al 2007), there have also been detections of molecules with (NH-C = O) peptide bond, like formamide (Rubin et al 1971), acetamide , and of other biologically relevant organic molecules like glycolaldehyde (the first sugar; Hollis et al 2000), urea (Remijan et al 2014), methyl acetate (Tercero et al 2013), acetaldehyde Fourikis et al 1974;Gilmore et al 1976), and amino acetonitrile (Belloche et al 2008).…”
Section: Introductionmentioning
confidence: 99%